Asuhan Keperawatan pada Tn. Z Dengan Gangguan Sistem Endokrin: Post OP Struma Nodusa Non Toksik di Ruang Mawar 2 RSUD Dr. Soeselo Kabupaten Tegal - Fayiko Yulia Muhfaj; Ahmad Zakiudin; Yusriani Saleh Baso; Sukirno Sukirno (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
The thyroid gland is an endocrine organ that has a dual role in regulating the level of metabolism and regulates fat and carbohydrate metabolism. The shape resembles a butterfly and is the largest gland in the human body (Jamal & Maracilu, 2023). The thyroid gland is in the front of the neck just below the larynx and sticks to the trachea. This gland has two lobes, namely the right lobe and the left lobe that is connected by Isthmus which is a small piece of tissue (Arsana, 2023). The thyroid gland produces important hormones such as T4 and T3 needed by the body for metabolic functions. The production of this hormone depends on the intake of iodine from food and salt (Dewi et al., 2023).